Clinical Characteristics and Mechanism Discussion of Peripheral Nerve Injury in 2 Cases of Severe Viral Meningoencephalitis - Guo X; Zheng M; Wei Z; Song J; Wang X; Shen Z; Guo X; Zhang N; Xing Y; Zhang Y; Zhang W; Du R; et al. (Journal of Inflammation Research)
Xiaosu Guo,1– 4,* Mengyi Zheng,1– 3,* Zibin Wei,1,3 Jianghua Song,1,3 Xue Wang,1,3 Zhiyuan Shen,1– 3 Xin Guo,1– 3 Nan Zhang,1– 3 Yuan Xing,1– 3 Yaxin Zhang,1– 3 Wei Zhang,1 Runxuan Du,5 Bo Qiu,5,6 Shujuan Tian,1– 3 Zhiwei Wang1,3 1Department of Neurology, the First Hospital of Hebei Medical University, Shijiazhuang, Hebei, People’s Republic of China; 2Department of Neurology, Neuromedical Technology Innovation Center of Hebei Province, Shijiazhuang, Hebei, People’s Republic of China; 3Department of Neurology, Hebei Hospital, Xuanwu Hospital of Capital Medical University, Shijiazhuang, Hebei, People’s Republic of China; 4Department of Neurology, Brain Aging and Cognitive Neuroscience Laboratory of Hebei Province, Shijiazhuang, Hebei, People’s Republic of China; 5Department of Reproductive Medicine, Hebei General Hospital, Shijiazhuang, Hebei, People’s Republic of China; 6Department of Pharmacy, Hebei General Hospital, Shijiazhuang, Hebei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shujuan Tian, Department of Neurology, The First Hospital of Hebei Medical University; Department of Neurology, Neuromedical Technology Innovation Center of Hebei Province; Department of Neurology, Hebei Hospital, Xuanwu Hospital of Capital Medical University, Shijiazhuang, Hebei, 050030, People’s Republic of China, Tel +86-0311-87156309, Email 57203005@hebmu.edu.cn Zhiwei Wang, Department of Neurology, The First Hospital of Hebei Medical University; Department of Neurology, Hebei Hospital, Xuanwu Hospital of Capital Medical University, Shijiazhuang, Hebei, 050030, People’s Republic of China, Tel +86-0311-87156309, Email 57803003@hebmu.edu.cnPurpose: Peripheral neuropathy(PN) secondary to central nervous system(CNS) infections is rare in clinical practice. This study analyze the prognosis, clinical characteristics, and outcomes of patients with PN secondary to CNS infections to aid early diagnosis and improve prognosis.Methods: Clinical data from two patients admitted to our Neurology Department with PN secondary to severe viral meningoencephalitis were collected, summarized, and analyzed. Using diagnostic tools like body fluid tests, imaging, EEG, and EMG, and based on the criteria of the International Encephalitis Consortium, encephalitis was diagnosed in Case 1 and Case 2. The European Academy of Neurology/Peripheral Nerve Society recommendations were applied to confirm patients’ PN diagnosis.Results: Patient 1 was diagnosed with encephalitis, presenting with elevated serum IL-6 levels, and received IVIG treatment upon admission. One week later, the infection remitted and IL-6 levels decreased. Physical and EMG examinations revealed peripheral nerve demyelination damage. After treatment, the nerve damage improved, and the patient had a good prognosis post-discharge. Upon admission, Patient 2 exhibited viral meningoencephalitis symptoms, with elevated serum IL-8 and normal IL-6 levels; limb muscle strength and tone were normal. Five days later, the infection deteriorated, accompanied by reduced lower limb strength, and elevated IL-6 and IL-8 in serum and CSF, with a striking peak of CSF IL-6. EMG confirmed peripheral nerve demyelination and axonal damage. Following 5-day IVIG treatment, IL-6 and IL-8 levels in serum and CSF declined. Peripheral nerve injury recovery was modest despite treatment, and the patient’s prognosis remained moderate.Conclusion: This study reported two rare cases of PN following CNS infection. Comparative analysis of symptoms, cytokine in body fluids, treatments, disease courses, and prognosis indicates that elevated peripheral and/or central cytokines, particularly IL-6 and IL-8, correlate with the severity and prognosis of this complication. IVIG modulates inflammation, and its administration timing likely determines differential outcomes.Keywords: viral meningoencephalitis, peripheral nerve injury, electromyography